HUBUNGAN DANA ALOKASI UMUM, BELANJA MODAL, PENDAPATAN ASLI DAERAH DAN PRODUK DOMESTIK REGIONAL BRUTO (Studi Pada Kabupaten / Kota di Propinsi Jawa Tengah) - Dwi Okto Imtichanah, 10.05.52.0065; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2014)
This study aimstoexamine the relationshipof general allocationfund, capital expenditures, incomearea andregional gross domestic productin2008-2011. to the district / kotamadia in central java province.The sample used inthis studyis thefinancial dataof local governmentdistrict /municipalityinthe province ofCentral Java. The data collection methodusedin this studypurposivesampling. The analytical tool usedismultiple linearregressiont test, ftest, andtest the coefficientof determination.The results of this study indicate that the variable general grants significant positive effect on capital expenditures, the general allocation fund variables significant positive effect on local revenues, capital expenditure variable significant positive effect on gross domestic regional product and regional income variable significant positive effect on product regional gross domestic.Keywords: allocation of GeneralFund, Capital Expenditure, RevenueRegionnative, regional gross domesticproduct